Experimental and Computational Investigation of an “Open” Transonic Cavity Flow - Atvars, K.; Knowles, Kevin; Ritchie, S. A.; Lawson, Nicholas J. (Cranfield University, 2009)
This paper presents an investigation of a transonic flow (M∞ = 0.85) over a rectangular cavity having a length-to-depth ratio of 5. Velocities were measured inside the cavity on the central plane and two off-centre planes using a two-component particle image velocimetry system. These measurements were supported by surface flow visualisation, and mean and time-varying surface pressure measurements. The flow was also simulated using an unsteady Reynolds-averaged Navier Stokes code, with a realizable κ− ε turbulence model. It is shown that this CFD model does not capture all the characteristics of the flow field correctly. However, by using this integrated experimental and computational approach we have been able to identify three-dimensional flow field structures within the cavity. The influence of the thickness of the approaching boundary layer is discussed.
Keywords: Transonic cavity; Flow-visualisation; PIV; URANS CFD